Ruling out clinically suspected pulmonary embolism by assessment of clinical probability and D-dimer levels: a management study - Leclercq, Monique G. L.; Lutisan, Johan G.; Marwijk Kooy, Marinus van; Kuipers, Bart F.; Oostdijk, Ad H. J.; van der Leur, Jef J. C. M.; Büller, Harry R. (Thrombosis and Haemostasis, 2003)
D-dimer test combined with clinical probability assessment has been proposed as the first step in the diagnostic work-up of patients with suspected pulmonary embolism (PE). In a prospective management study we investigated the safety and efficiency of excluding PE by a normal D-dimer combined with a low or moderate clinical probability. Of the 202 study patients this combination ruled out PE in 64 (32%) patients. The 3-month thromboembolic risk in these patients was 0% (95% CI, 0.0-5.6%).The prevalence of PE in the entire cohort was 29% (59 patients), whereas in the low, moderate and high clinical probability groups this was 25%, 26% and 50%, respectively. We conclude that ruling out suspected PE by a normal D-dimer combined with a low or moderate clinical probability appears to be a safe and efficient strategy. The accuracy of the clinical probability assessment is modest.
Keywords: Pulmonary embolism; management; diagnosis; D-dimer; clinical probability